Cytoreductive surgery for head and neck squamous cell carcinoma in the new age of immunotherapy. (October 2016) - Bell, R. Bryan; Gough, Michael J.; Seung, Steven K.; Jutric, Zeljka; Weinberg, Andrew D.; Fox, Bernard A.; Crittenden, Marka R.; Leidner, Rom S.; Curti, Brendan
Highlights: Patients who develop local-regional disease progression in conjunction with distant metastasis have few good palliative options available to achieve local tumor control and/or relieve symptoms. The goal of cytoreductive surgery is to minimize tumor-induced immune suppression by reducing the number of cancer cells via resection of primary tumor or metastatic deposits, to palliate symptoms, and prevent complications. We hypothesize that surgical resection can be combined with immunotherapy to induce an effective immune response and overcome immunosuppression in the tumor microenvironment. Abstract: Cytoreductive surgery is an approach to cancer treatment that aims to reduce the number of cancer cells via resection of primary tumor or metastatic deposits, in an effort to minimize a potentially immunosuppressive tumor burden, palliate symptoms, and prevent complications. Furthermore, it provides a platform for investigation of biomarkers with the goal of optimizing immunotherapy to reverse the immunosuppressive tumor microenvironment and enhance adaptive immune responses. Ultimately, our group aims to exploit the concept that successful cancer therapy is dependent upon an effective immune response. Surgery will remain an integral part of head and neck squamous cell carcinoma (HNSCC) treatment in the future, even as checkpoint inhibitors, co-stimulatory molecules, vaccines, adoptive T cell therapy and other novel agents enter clinical routine. Cytoreductive resection may provide an effective platform for immunotherapy and biomarker directed interventions to improve outcomes for patients with HNSCC.